Trichilemmal cysts of scalp: Imaging findings - Narra, Ramakrishna; Kamaraju, Sushil Kumar; Putcha, Anusha (Indian Journal of Case Reports, 2018)
A trichilemmal cyst is a cystic lesion that forms from the hair follicle. They are also known as Wens. They are smooth nodular mobile swellings of the scalp which may be tender or non-tender and may run in families. Usually multiple, they are common in the occipital scalp region but can also occur in chest, abdomen, back, vulva, and pubis. Here, we present the case report of a 45-year-old woman with multiple trichilemmal cysts of the scalp.